2007
DOI: 10.1111/j.1744-313x.2007.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CD28 and CTLA‐4 gene polymorphisms in Turkish patients with Behcet's disease

Abstract: In this study we aimed to investigate IVS3 +17T/C single nucleotide polymorphism (SNP) of CD28 gene, +49A/G and -318C/T SNPs of CTLA-4 gene in patients with Behçet's disease (BD) and their potential association to the main clinical features of the disease. These polymorphisms were investigated in a Turkish population of 123 patients with BD and 179 healthy controls, by using PCR-RFLP technique. HLA-B*51 genotype was also studied in both groups by using PCR-SSP. The frequency of IVS3 +17TC genotype of the CD28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
4
47
2
Order By: Relevance
“…Although CD28 SNPs have been related to alterations in mRNA splicing and transcription factor binding [10,52], no significant association was found between PF disease status and CD28 polymorphisms analyzed either individually or in haplotypes. Associations were found with BehÈet's disease and idiopathic ischemic stroke [8,9]. However, in accordance with our results, CD28 polymorphisms seemingly also do not influence susceptibility to various diseases, including autoimmune thyroid diseases and autoimmune hepatitis [53,54].…”
Section: Discussionsupporting
confidence: 88%
“…Although CD28 SNPs have been related to alterations in mRNA splicing and transcription factor binding [10,52], no significant association was found between PF disease status and CD28 polymorphisms analyzed either individually or in haplotypes. Associations were found with BehÈet's disease and idiopathic ischemic stroke [8,9]. However, in accordance with our results, CD28 polymorphisms seemingly also do not influence susceptibility to various diseases, including autoimmune thyroid diseases and autoimmune hepatitis [53,54].…”
Section: Discussionsupporting
confidence: 88%
“…Baranathan et al (2007) reported that protein tyrosine phosphatase type 22 (PTPN22 620W) was inversely associated with BD susceptibility. Gunesacar et al (2007) reported that SNP of the CD 28 gene was increased in BD patients, whereas the CTLA-4 gene was decreased. With regard to intestinal BD, however, there have been no reports on genetic polymorphisms.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is known that this polymorphic site is within the region where regulatory elements could bind, influencing the mRNA splicing efficiency and consequently changing the expression of the CD28 molecule [61]. The distribution of alleles and genotypes of the CD28 gene polymorphism in patients with schizophrenia is similar to that found in patients with autoimmune disorders such as early-onset type 1 diabetes [62] and Behçet's disease [63]. On the other hand, in the study of rheumatoid arthritis there is an inverse distribution of alleles and genotypes of the CD28 gene polymorphism that was found in our group of schizophrenia patients [64].…”
Section: Discussionmentioning
confidence: 56%